Comparison of Questionnaire Scales to Assess the Function of the Shoulder Joint in Patients after Unipolar Arthroplasty - Strafun, S.S.; Haiovych, V.V.; Zanko, I.S. (TERRA ORTHOPAEDICA, 2021)
Summary. Unipolar shoulder arthroplasty is the method of choice for multifragmental fractures of the humeral head, aseptic necrosis of the humeral head, and deforming arthrosis of the humeral joint grade 3-4 by Kellgren and Lawrence. There are many rating scales for monitoring the recovery of shoulder joint function after unipolar arthroplasty during the rehabilitation stages. Common and most popular are: UCLA (University of California, Los Angeles) Shoulder Rating; Constant-Murley Score; DASH (Disabilities of the Arm, Shoulder and Hand); ASES (American Shoulder and Elbow Surgeons) Score; Oxford Shoulder Score, Constant Shoulder Score, and others. Each of them has its advantages and disadvantages. Objective: to conduct a comparative analysis of modern assessment scales for assessing the function of the shoulder joint in patients after unipolar arthroplasty. Materials and Methods. Comparative analysis was performed in 50 patients after unipolar arthroplasty with the consequences of injuries of the shoulder joint of varying severity. Patients filled in the answers to the questions of four proposed rating scales before treatment and further in dynamics 6 and 12 months after the surgical intervention. The share of males in the cohort of respondents was 40.5%; females were 59.5%. Four most common scales in the world practice were chosen. The average age of male patients was 62±11.4 years; the average age of female patients was 66±10.1 years. The patients underwent unipolar prosthesis of the shoulder joint: 30 patients (60%) after traumatic injuries of the proximal epimetaphysis of the humerus, 9 patients (18%) after deforming osteoarthritis, and 11 patients (22%) after aseptic osteonecrosis. Results and Conclusions. We analyzed the results of treatment of 50 patients at different times after unipolar arthroplasty using four assessment systems (Oxford Shoulder Score, Constant Shoulder Score, ASES, and SPADI) of shoulder function. According to the results of the analysis, in our opinion, the Constant Shoulder Score was the most informative system, as it includes both subjective and objective parts and not only quantitative characteristics, but also qualitative criteria for evaluating the results of treatment. Other rating scales turned out to be less objective.